Complete sequence of mitochondrial genome of Cucumis melo L. Issue 3 (2nd July 2020) - Ding, Zhuo; Cui, Haonan; Zhu, Qianglong; Wu, Yue; Zhang, Taifeng; Qiu, Boyan; Gao, Peng
Abstract: Cucumis melo L. is one of the most important fruit-type vegetables in the world. This genome is divided into a main loop and two small loops. The length of the main loop is 2, 709, 526 bp, and the two small loops are 149, 555 bp and 47, 592 bp long, respectively. There are 88 coding genes in the melon mitochondrial genome, including 40 protein-coding genes (which accounted for about 1.23% of the whole genome), 8 rRNAs, and 40 tRNAs. The total length of rRNAs and tRNAs spans 0.31% of the total genome sequence. Among the 88 mitochondrial coding genes, only 5 tRNAs were located into the second largest circular DNA molecule. The complete mitogenome sequence provided herein would help understand C. melo evolution.